HER2/p53 ratios among canine mammary tumours and respective derived cell culture - Sakamoto, Silmara Sanae; Panegossi, Letícia Colin [UNESP]; De Carvalho, Roberto Gameiro [UNESP]; Cardoso, Tereza Cristina [UNESP] (Malque Publishing, 2022)
In this study, the expression of p53 and human epidermal growth factor receptor 2 (HER2) proteins were investigated in different canine mammary tumors (CMT) and cell cultures derived from them, for the purpose of determining neoplastic behavior in vitro. For this purpose, immunohistochemistry and immunocytochemistry were performed and results were compared according to histological diagnose. CMT were collected and divided into two halves, one for histological and immunohistochemistry analyses and another for cell cultures. Cell markers p53 and HER2 proteins were detected by immunohistochemistry in the original tumors and immunocytochemistry in CMT-derived cell lines. A total of CMT (n = 17) were classified and divided into benign mixed tumor (BMT), complex carcinoma (CC), simple carcinoma (SC), and squamous cell carcinoma (SCC). Low expression of p53 was verified in BMT and CC, averagely in SC and undetectable in SCC. In vitro, there was an increase in p53 expression by cultured cells. However, HER2 protein expression was not significant in BMT, CC and SCC. In contrast, MCT-derived cells were considered HER2-positivein all MCT types. In conclusion, the in vitro model is essential for the study of neoplastic behavior and understanding of the carcinogenic mechanisms that occur in vivo.
Keywords: cancer markers; cell phenotype; In vitro culture